Mercury in sediment and freshwater organisms from Kr. Sikulat River around the artisanal gold mining plants in Sawang, Aceh Province, Indonesia - . Suhendrayatna; . Elvitriana (Syiah Kuala University, 2012)
Artisanal gold miners in Sawang use mercury in gold separation process. The workers put gold ore and mercury into the tumblers to extract gold and silver by amalgamation method. After gold and silver are isolated from the ore as amalgam, mercury is vaporized by burning with an oil burner. Furthermore, wastewater containing mercury is discharged at landfills and Kr. Sikulat River stream. With the purpose of knowing the impact of small-scale gold mining plant in Sawang, the concentrations of mercury in Kr. Sikulat River sediment and the accumulation of mercury in tissues of freshwater organisms from Kr. Sikulat River were investigated. Sediments were taken from locations near the gold mining plant and freshwater organisms were caught in the estuary from Kr. Sikulat River. Samples were transported live to the laboratory and sampled dissected after death. Tissue from each organism were removed and grained after dried. Total mercury analyzed using an Atomic Absorption Spectrometry (AAS), AA-6300 Shimadzu. The results showed that the concentration of mercury in sediment found 0.0339 mg-Hg/kg, while the concentration of mercury in the water phase were found 0.005 – 0.047 mg-Hg/L. Mercury was also found in the concentration of 0.1903 mg-Hg/kg accumulated in the shellfish, but it was not found accumulated in other freshwater organisms such as fish and shrimp. Based on these results, a regular monitoring program in Kr. Sikulat River is necessary conducted in order to better elucidate the rate of bioaccumulation and biomagnification by organisms